The Impact of Mobile-Assisted Language Learning on EFL Students' Presentation Skills - Riska Awaliyah; Ashadi Ashadi (Pedagogy Review, 2026)
Mobile-Assisted Language Learning (MALL) has emerged as a transformative catalyst in facilitating English as a Foreign Language instruction, particularly in enhancing speaking competencies. The primary objective of this study was to investigate the impact of MALL on EFL students’ presentation skills, focusing on how mobile technologies foster student-centered learning environments. By exploring the intersection of digital tools and pedagogical frameworks, the research sought to identify how mobile applications facilitate the development of complex speaking tasks. To achieve this, the study employed a mixed-method research design, integrating both quantitative and qualitative data to provide a comprehensive analysis of the phenomenon. The quantitative phase involved thirty-eight students from Universitas Negeri Yogyakarta, focusing on their use of various MALL applications to prepare for presentations. Data were analyzed using descriptive statistics to identify trends in proficiency gains. Simultaneously, the qualitative phase utilized semi-structured interviews and descriptive techniques to capture nuanced student experiences and perceptions. The findings of this study indicate that the integration of MALL substantially improves several key dimensions of oral proficiency, including pronunciation, vocabulary acquisition, and grammatical accuracy. Furthermore, mobile tools were found to be instrumental in helping students structure their presentation content and significantly bolster their self-confidence. The results suggest that the core drivers of these improvements are the opportunities for repeated, self-directed practice and the availability of immediate feedback provided by mobile platforms. Consequently, learners exhibited heightened motivation and a stronger willingness to engage in challenging speaking activities. In conclusion, this research emphasizes that when MALL is thoughtfully implemented with appropriate pedagogical scaffolding, it can significantly strengthen EFL students’ presentation skills and overall speaking fluency. The study suggests that educators should move beyond mere technology adoption, focusing instead on integrating MALL as a strategic component of communicative language teaching to foster autonomous, confident language learners. Keywords: EFL learner, MALL, presentation skill, speaking skill